Relationship between Reaction Kinetics and Chain Dynamics of Vitrimers Based on Dioxaborolane Metathesis - Wu, Shilong; Yang, Huanhuan; Huang, Shaoyong; Chen, Quan (Macromolecules, 2020)
Processability of vitrimers strongly relies on the temperature dependence of viscosity. In this study, we analyzed temperature-dependent viscoelasticity of vitrimers based on the dioxaborolane metathesis reaction. A sol-to-gel transition process and a reverse gel-to-sol process are observed in the linear viscoelasticity with increasing content of the cross-linker. The latter gel-to-sol process is owing to a reverse reaction between a two-site interchain cross-linking point with an excess cross-linker, forming two noncross-linking sites. For samples above the gel point, the increasing temperature leads to a weaker acceleration of the decross-linking process than the Rouse-type relaxation, and accordingly, broadening of the plateau region. This trend is easily visualized in samples slightly above the gel point for which the stress relaxation arising from the Rouse-type relaxation and the decross-linking process are not well separated over time. This temperature-dependent behavior reflects a case that the lifetime of the dynamic covalent bond is significantly larger than the Rouse time of the network strands. As a result, the stress borne by a strand relaxes immediately upon decrosslinking, and thus, the low activation energy of the dioxaborolane metathesis reaction governs the strand relaxation.